Religious Freedom in Transition: Spain - Oliva, Javier García (Religion, state & society, 2008)
After a peaceful and well-conducted transition towards democracy (1975-78), the Spanish Constitution was enacted in December 1978. This article starts with the events which led to the Civil War (1936-39) and studies the relationship between the Spanish state and the Catholic Church throughout Franco's dictatorship. This background is necessary for a proper understanding of the current legal framework on religion, which is the main aim of this article. In the light of the pronouncements of the Spanish Constitutional Court (SCC), I analyse the various paragraphs of Article 16 of the Constitution, especially with regard to the position of individuals and communities. I also deal with the relationship between religious freedom and ideological freedom. I offer a critical judgment on the position of the Catholic Church and the other religious denominations which concluded agreements with the Spanish state in 1992. Finally, I highlight current trends, particularly the difficult relationship between the socialist government and the Catholic Church in the last few years. Although the situation had significantly improved by 2007, there are still occasions on which tension between the two institutions is manifest.